Endoscopic Management of Gastric Variceal Bleeding with Cyanoacrylate Glue Injection: Safety and Efficacy in a Canadian Population - Jaber Al-Ali; Monika Pawlowska; Alan Coss; Sigrid Svarta; Michael Byrne; Robert Enns (Canadian Journal of Gastroenterology)
BACKGROUND: Gastric variceal bleeding (GVB) is a major cause of morbidity and mortality among patients with portal hypertension. Endoscopic band ligation and standard sclerotherapy have been used but have significant limitations. Decompression through transjugular intrahepatic portosystemic shunt insertion has been shown to be effective. Gastric variceal injection therapy with a commercially available cyanoacrylate glue is less invasive than transjugular intrahepatic portosystemic shunt insertion and has recently been shown to be effective for acute hemostasis.